2016
DOI: 10.1177/2054358116679131
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Incremental Peritoneal Dialysis in a Large Contemporary Peritoneal Dialysis Program

Abstract: Background:The use of an incremental peritoneal dialysis (PD) strategy in a large contemporary patient population has not been described.Objective:We report the use of this strategy in clinical practice, the prescriptions required, and the clearances achieved in a large center which has routinely used this approach for more than 10 years.Design:This is a cross-sectional observational study.Setting:A single large Canadian academic center.Patients:This study collected data on 124 prevalent PD patients at a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 27 publications
0
40
0
2
Order By: Relevance
“…Clearance targets drive PD prescription practices but less so than in HD. Incremental strategies are increasingly used (17). Icodextrin is widely used, but normal pH "biocompatible" solutions are not, partly due to higher cost and uncertain evidence.…”
Section: Home Dialysis Practicesmentioning
confidence: 99%
“…Clearance targets drive PD prescription practices but less so than in HD. Incremental strategies are increasingly used (17). Icodextrin is widely used, but normal pH "biocompatible" solutions are not, partly due to higher cost and uncertain evidence.…”
Section: Home Dialysis Practicesmentioning
confidence: 99%
“…In an attempt to retain residual renal function, incremental PD may be a viable option. 32 Last, several studies have reported that survival and long-term therapy outcomes of ADPKD patients on PD did not differ significantly against matched non-ADPKD controls, 33 , 34 with 1 study reporting a notably high survival rate. 34 This was consistent with our findings that ADPKD patients with PD as an initial therapy demonstrated improved survival compared with non-ADPKD patients.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, there is one observational study reporting that for an elderly cohort, there are less frequent episodes of hospitalization with twice‐weekly hemodialysis . Similar approaches in peritoneal dialysis, using days‐off and/or a reduced number of exchanges have also been shown to deliver adequate Kt/V, do not appear to be associated with worse mortality and may be associated with lower hospitalization rates …”
Section: Conventional Dialysis In the Elderly: How Do We Rewrite Our mentioning
confidence: 99%
“…48 Similar approaches in peritoneal dialysis, using days-off and/or a reduced number of exchanges have also been shown to deliver adequate Kt/V, do not appear to be associated with worse mortality and may be associated with lower hospitalization rates. 49,50 The use of incremental dialysis and the associated reduction in dialysis burden enabled by residual renal function is likely to improve patient experience and therefore patient outcomes. Preservation of residual renal function should therefore be incorporated into guidelines for dialysis delivery in older people.…”
Section: Residual Renal Function and Incremental Dialysismentioning
confidence: 99%